An assessment of the implementation of the pneumococcal conjugate vaccination program for Aboriginal and Torres Strait infants in North Queensland - Hanna, Jeffrey N; Bullen, Ruth C; Ziegler, Clare L; Akee, Tanya; Dostie, Brigitte G; Lort-Phillips, Kathy (Communicable Diseases Intelligence, 2003)
A cohort of 199 Aboriginal and Torres Strait Islander infants, born in north Queensland in August and September 2002, were followed-up to ascertain the uptake of the 7-valent pneumococcal conjugate vaccine (7vPCV) by certain ages. Although 70 per cent of the cohort had received a dose of 7vPCV by three months, only 50 per cent had received three doses by seven months. Most (approximately 90%) of the children who received the vaccine by three and five months were given it at the same time as the other two scheduled injectable vaccines, and most (84%) of the children received three doses of 7vPCV by 12 months of age. However, 18 per cent of the cohort had not received any vaccines (other than those given at birth), another 10 per cent had received the other scheduled vaccines but no 7vPCV by three months of age, and 38 per cent had received the other vaccines but not two doses of 7vPCV by five months. A variety of measures are described that have been put in place to attain optimal coverage of Aboriginal and Torres Strait Islander infants in north Queensland with 7vPCV and to improve timeliness. Commun Dis Intell 2003;27:262-266.